Literature review: Ubi Jalar Ungu sebagai Bahan Makanan Tambahan Remaja Kurang Energi Kronis - Setyawati, Irni; Soekmawaty Riezqy Ariendha, Dian; Utami, Kusniyati; Handayani, Sri (Jurnal Ilmiah STIKES Yarsi Mataram, 2022)
The quality of the nation's next generation is largely determined by adolescent girls who act as future mothers. The physical and psychological maturity of adolescent girls greatly affects a woman's readiness to become a mother in a healthy family. Basic health research data (Riskesdas) in 2018 reported that west Nusa Tenggara (NTB) province had women aged >18 years thin based on BMI as much as 12%, and Mataram city had the second most thin >18 years old women (14.02%) after North Lombok district which was 15.99%. An initial survey conducted on 20 female students at STIKes Yarsi Mataram in February 2021 found that 30% of female students had Lila <23.5 cm. This situation shows that not all female students at STIKes Yarsi Mataram have a good nutritional status. This study aims to identify the nutritional status of STIKes Yarsi Mataram students as an early detection of chronic lack of energy events in the health college environment. This study used an observational descriptive design with a cross-sectional approach. The population of this study is students of the Nursing study program at the D3 level, the midwifery study program at the D3 level and the undergraduate program in semesters 1 and 3 at STIKes Yarsi Mataram. The sample was taken using purposive sampling techniques for 1st and 3rd semester students who used offline learning methods and were not practicing outside the campus with a total of 176 female students. The primary data taken are in the form of BB, TB, and Lila. This research was conducted in September 2021 - January 2022 at STIKes Yarsi Mataram. The results of this study found thata large number of STIKes Yarsi Mataram students had a normal BMI (18.5-25), although there were a small number of female students who had a thin BMI (<18.5) and a fat BMI (>25). Most of the students of STIKes Yarsi Mataram have a normal Lila (>23.5 cm), but the rest have a risk Lila of SEZ (<23.5 cm). It is hoped that there will be an intensive increase in the knowledge, attitudes and behaviors of female students about diet, nutrient intake and body image from lecturers in collaboration with nutritionists.